Cash Waqf Linked Sukuk (CWLS): An Alternative Instrument for Infrastructure Financing - Ubaidillah, Ubaidillah; Masyhuri, Masyhuri; Wahyuni, Nanik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Sukuk and waqf become an important component and contribute for the development of a country. The evidence of the success of waqf is seen in their contribution to the public interest, therefore waqf institutions are required to achieve it. In realizing the goal of creating productive waqf instruments, BWI and several stakeholders have created the Cash Waqf Linked Sukuk (CWLS) isntrument. This aims to encourage the consolidation of Islamic social funds and provide a safe social-based investment space, so far CWLS has contributed to the health sector as happened in hospitals. Achmad Wardi Attack Banten. This instrument also has great potential to cover the state budget deficit in meeting the financing of state infrastructure development. This paper uses descriptive qualitative method with literature review. it tries to explore the Cash Waqf Linked Sukuk as a potential instrument that can contribute positively to social welfare in Indonesia.